Study of the Role of Construction Companies on the K3 Management System as an Effort to Improve the Quality of the Company - Nurjanah; Hangga Prima Setiawan; Bambang Hardadi; Iqbal Novarino (Civilla : Jurnal Teknik Sipil Universitas Islam Lamongan, 2024)
Measurement of construction companies can be declared good if implementing the Occupational Health and Safety Management System (OHSAS). Meanwhile, the most important element in the OHSAS implementation program is the company's policy on designing the construction work safety system or support from the Board of Directors for the implementing occupational safety design. This study aims to check the influence of the company's owner on the OHSA quality of the company. The survey was followed by distributing questionnaires to several construction company owners in Blitar for data collection. It was taken to determine whether this research is very influential or not at all regarding the importance of the company's owner's role regarding OHSA and the application of protective equipment to reduce work accidents on the quality and competitiveness of the company in the construction project auction in the construction project for private, local, and national governments. The results of the study showed superiors and directors of construction service companies whose roles and responsibilities have not been maximized in implementing the company’s occupational health and safety management system in Blitar. In this case, the implementation of OHSA by the company indirectly contributes to maintaining the quality of the services provided.